Structural assessment of a masonry vault in Portugal - Lança, Pedro Daniel Neto (2015)
This paper reports on a structural safety assessment and performance evaluation of the upper choir of the Santa Maria de Belém Church in the Jerónimos monastery, Lisbon, one of the most important cultural heritage buildings in Portugal. The possibility of adding a new 20 t organ to the upper choir and its effects on the church structure's response are presented. A refined and a simplified finite-element model is developed to investigate the structure's performance under self-weight and seismic actions. A sensitivity analysis is performed to investigate the effect of masonry mechanical properties and rib cross-sections on the structural response, given the difficulty in accurately obtaining this information. The results show that the safety level of the structure is acceptable, even in the case of adding a heavy new organ.